INVESTIGATING THE NATURE, PURPOSE AND EFFECTIVENESS OF BUSINESS RESCUE IN SOUTH AFRICA: CHAPTER 6 OF COMPANIES ACT 71 OF 2008 AS AMENDED (Singaporean Journal of Business Economics and Management, 2016)
The Companies Act 71 of 2008 was passed by parliament on the 19 November 2008 and assented to by the president on the 8 April 2009. The Act came into force on the 1 May 2011 and it contains provisions of Business Rescue which abolished the provisions of judicial management under the Companies Act 61 of 1973. The Business Rescue has become an important part of South African Business environment since it replaced its predecessor which had a lower success rate. Since Business Rescue is fairly new, our courts are still finding their feet with regards to the provisions of this Act. Due to recent case decision that shows that the provisions cannot be relied upon unconditionally without proper regard to the circumstances of each case, the research provides an insight on how Business Rescue works, whether it serves the purpose it was intended to achieve and how effective it is.